Good Corporate Governance Moderate Environmental Performance And Disclosure Corporate Social Responsibility On Economic Performance - Lindawati, Lindawati; Holiawati, Holiawati; Rosini, Iin (SEAN Institute, 2024)
This research aims to test and analyze good corporate governance moderating environmental performance and Corporate Social Responsibility disclosure on economic performance in Kompas 100 indexed companies listed on the Indonesia Stock Exchange from 2019 to 2022. This type of research is associative quantitative research using secondary data. The data analysis method used is a panel data regression test using Microsoft Excel and Eviews 10 applications. The population in this study is all Kompas 100 indexed companies listed on the Indonesia Stock Exchange from 2018 to 2022. The data collection technique in this research is purposive. Sampling with results from 100 research populations resulted in 21 research samples being processed in this research. The research results show that environmental performance and disclosure of Corporate Social Responsibility influence economic performance. The following result is that environmental performance does not affect economic performance, whereas Corporate Social Responsibility disclosure affects economic performance. For Good Corporate Governance, it can strengthen the relationship between environmental performance and economic performance. In contrast, the results show that Good Corporate Governance does not moderate the relationship between corporate social responsibility disclosure and economic performance.